2019
DOI: 10.1186/s41235-019-0156-5
|View full text |Cite
|
Sign up to set email alerts
|

How does navigation system behavior influence human behavior?

Abstract: Navigation systems are ubiquitous tools to assist wayfinders of the mobile information society with various navigational tasks. Whenever such systems assist with self-localization and path planning, they reduce human effort for navigating. Automated navigation assistance benefits navigation performance, but research seems to show that it negatively affects attention to environment properties, spatial knowledge acquisition, and retention of spatial information. Very little is known about how to design navigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 60 publications
1
31
2
1
Order By: Relevance
“…It could be that more GPS use decreases spatial transformation abilities or that decreases in spatial transformation abilities lead to increased GPS use. GPS use may also decrease environmental learning indirectly through alternative paths not measured in the current study, such as navigational style (Richter, Dara-Abrams, & Raubal, 2010) or human gaze behavior (Brügger, Richter, & Fabrikant, 2019). However, the current results are an informative first step in broadly establishing a negative association between everyday GPS use and environmental learning while also identifying spatial transformation abilities as a potential mediating factor in this relationship.…”
Section: Discussionmentioning
confidence: 54%
“…It could be that more GPS use decreases spatial transformation abilities or that decreases in spatial transformation abilities lead to increased GPS use. GPS use may also decrease environmental learning indirectly through alternative paths not measured in the current study, such as navigational style (Richter, Dara-Abrams, & Raubal, 2010) or human gaze behavior (Brügger, Richter, & Fabrikant, 2019). However, the current results are an informative first step in broadly establishing a negative association between everyday GPS use and environmental learning while also identifying spatial transformation abilities as a potential mediating factor in this relationship.…”
Section: Discussionmentioning
confidence: 54%
“…In the wayfinding process, different methods for information acquisition afford different types of spatial knowledge (Afrooz, White, and Parolin 2018;Brügger, Richter, and Fabrikant 2019). In particular, the active acquisition of environmental information by wayfinders was determined to yield information of greater depth and quantity (Afrooz, White, and Parolin 2018).…”
Section: Wayfindingmentioning
confidence: 99%
“…In particular, the active acquisition of environmental information by wayfinders was determined to yield information of greater depth and quantity (Afrooz, White, and Parolin 2018). Brügger, Richter, and Fabrikant (2019) noted that for participants who used electronic navigators, greater automation in the electronic navigator resulted in a lesser acquisition of spatial information. Additionally, the study revealed that when returning to the starting point through the path taken, greater automation in the electronic navigator resulted in a greater frequency of stopping and hesitating in participants.…”
Section: Wayfindingmentioning
confidence: 99%
“…For example, the effects of variables, such as gender and age, have been omitted even if these factors are known to influence navigational use and skills [20]. Furthermore, little work has been done on how navigation aids influence walkability [10] and very little is known about the role that pedestrian navigation systems have on navigation performance and spatial cognition [21].…”
Section: Introductionmentioning
confidence: 99%